KEPEMIMPINAN DIGITAL: ANALISIS BIBLIOMETRIK [DIGITAL LEADERSHIP: BIBLIOMETRIC ANALYSIS] - Ahmad Setiyono; Puspa Devi Maharani; Suyanto - (Universitas Pelita Harapan, 2023)
The purpose of this study is to provide a literature review with an extensive bibliometric analysis of digital leadership developments so far, the main streams, which channels are most influential, and research network models in digital leadership studies. Search and collect articles using the Scopus Database with the keyword